A conjugated alkyne functional bicyclic polybenzoxazine with superior heat resistance. Issue 14 (20th June 2019) - Li, Pengcheng; Dai, Jie; Xu, Yi; Ran, Qichao; Gu, Yi
ABSTRACT: A difunctional benzoxazine (coPh‐apa) with a conjugated alkyne group is synthesized by the oxidative coupling reaction from a monocycle‐benzoxazine (Ph‐apa) containing an alkyne group. A model compound, 1, 4‐diphenylbutadiyne (coPa), is used to study the curing reaction process of coPh‐apa by DSC, Fourier transform infrared spectroscopy, and 13 C NMR, and the results suggest that the conjugated alkyne groups are involved in the crosslinking reaction via the trimerization reaction of the conjugated alkynyl groups and the Diels–Alder reaction. Furthermore, thermal properties of the polybenzoxazine are studied by dynamic thermomechanical analysis and thermogravimetric analysis. A glass‐transition temperature ( T g s) of as high as 412 °C and a char yield of 75.6% at 800 °C under nitrogen are obtained with the aid of the conjugated alkyne groups. Its excellent heat resistance dominates most thermosetting resins and will serve for heat shields. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 1587–1592 Abstract : A new benzoxazine (coPh‐apa) with a conjugated alkyne group was synthesized, and its polymer showed excellent heat resistance. A glass transition temperature of as high as 412 °C and a char yield of 75.6% at 800 °C under nitrogen were obtained, which should be attributed to the trimerization reaction of the conjugated alkynyl groups and the Diels–Alder reaction. Such an excellent heat resistance is useful in heat shielding materials.